Bauxite Resource Estimation Analysis Using Ordinary Kriging and Inverse Distance Weighting in West Kalimantan - Wahid, Muhammad Abdul; Winarno, Eddy (Journal of Earth and Marine Technology (JEMT), 2024)
PT X is a mining company engaged in bauxite mining which is located in Nanga Tayap District, Ketapang Regency, West Kalimantan Province. Currently the company is carrying out further exploration activities to find potential bauxite resources which will later be upgraded into reserves for mining. In resource estimation, there are several methods that can be used, such as the Nearest Neighbor Point method, Inverse Distance Weighting, and Ordinary Kriging. This research aims to analyze two resource estimation methods, namely Inverse Distance Weighting and Ordinary Kriging for resource estimation and choose the best method based on geological conditions and RMSE value parameters. Based on the results of this research, the estimated value of bauxite resources using the IDW method obtained a tonnage of 1,046,874.99 tons with an average Al₂O₃ content of 47.28%. Meanwhile, the estimated bauxite resource value using the OK method obtained a tonnage of 1,046,875.01 tonnes with an average Al₂O₃ content of 48.15%. Based on the calculation of the Root Mean Squared Error (RMSE) value from the two methods, the respective RMSE values were obtained, namely IDW = 0.0001263 and OK = 0.0084145. From these results it can be concluded that the best method for estimating bauxite resources in the Enggang block is the Inverse Distance Weighting (IDW) method.